Prognostic Significance of Overexpressed p16(INK4a) in Patients with Cervical Cancer: A Meta-Analysis - Lin, Jiaying (Public Library of Science, 2014)
BACKGROUND: p16(INK4a) is a tumor suppressor protein which is induced in cells upon the interaction of high-risk HPV E7 with the retinoblastoma protein by a positive feedback loop, but cannot exert its suppressing effect. Previous reports suggested that p16(INK4a) immunostaining allows precise identification of even small CIN or cervical cancer lesions in biopsies. The prognostic value of overexpressed p16(INK4a) in cervical cancer has been evaluated for several years while the results remain controversial. We performed a systematic review and meta-analysis of studies assessing the clinical and prognostic significance of overexpression of p16(INK4a) in cervical cancer. METHODS: Identification and review of publications assessing clinical or prognostic significance of p16(INK4a) overexpression in cervical cancer until March 1, 2014. A meta-analysis was performed to clarify the association between p16(INK4a) overexpression and clinical outcomes. RESULTS: A total of 15 publications met the criteria and comprised 1633 cases. Analysis of these data showed that p16(INK4a) overexpression was not significantly associated with tumor TNM staging (I+II vs. III+IV) (OR = 0.75, 95% confidence interval [CI]: 0.35–1.63, P = 0.47), the tumor grade (G1+ G2 vs. G3) (OR = 0.78, 95% CI: 0.39–1.57, P = 0.49), the tumor size (<4 vs. ≥4 cm) (OR = 1.10, 95% CI: 0.45–2.69, P = 0.83), or vascular invasion (OR = 1.20, 95% CI: 0.69–2.08, P = 0.52). However, in the identified studies, overexpression of p16(INK4a) was highly correlated with no lymph node metastasis (OR = 0.51, 95% CI: 0.28–0.95, P = 0.04), increased overall survival (relative risk [RR]: 0.42, 95% CI: 0.24–0.72, P = 0.002) and increased disease free survival (RR: 0.60, 95% CI: 0.44–0.82, P = 0.001). CONCLUSIONS: This meta-analysis shows overexpression of p16(INK4a) in cervical cancer is connected with increased overall and disease free survival and thus marks a better prognosis.